1986
DOI: 10.1203/00006450-198609000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cromolyn Sodium Decreases the Pulmonary Vascular Response to Alveolar Hypoxia in Lambs

Abstract: ABSTRACT. We investigated the effect of cromolyn sodium, a mast cell stabilizing agent, on the pulmonary vascular response to alveolar hypoxia in six chronically instrumented lambs aged 9 to 11 days. Each lamb was instrumented on day 6 or 7 for measurements of systemic arterial, pulmonary arterial and left atrial pressures, and pulmonary blood flow. The animals were allowed to recover from surgery at least 3 days before they were studied. Each animal was studied twice, once with a cromolyn sodium infusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Further evidence for mast cell involvement in hypoxia has come from studies using drugs that stabilize or activate mast cells. Use of the mast cell stabilizer cromolyn was associated with a reduction in hypoxia‐induced leukocyte adhesion (105, 106) and pulmonary arterial pressure and vascular resistance (107). Activation of mast cells in the normoxic situation by compound 48/80 mirrored the effect of hypoxia on leukocyte adhesion, and this effect was similarly blocked by mast cell stabilizers (105).…”
Section: Role Of Ros In Hypoxia‐induced Inflammationmentioning
confidence: 99%
“…Further evidence for mast cell involvement in hypoxia has come from studies using drugs that stabilize or activate mast cells. Use of the mast cell stabilizer cromolyn was associated with a reduction in hypoxia‐induced leukocyte adhesion (105, 106) and pulmonary arterial pressure and vascular resistance (107). Activation of mast cells in the normoxic situation by compound 48/80 mirrored the effect of hypoxia on leukocyte adhesion, and this effect was similarly blocked by mast cell stabilizers (105).…”
Section: Role Of Ros In Hypoxia‐induced Inflammationmentioning
confidence: 99%
“…Results from this study and our previous work (12), as well as studies in adult sheep (4,13), dogs (10, 1 I), and rats (3) suggest that CS alters the sequence of events that leads to HPV. Additionally, the efficacy of lower doses of aerosolized CS in attenuating the physiologic response to HPV support a local site of action for the drug similar to that postulated for its local action in the treatment of asthma (2 1).…”
Section: Discussionmentioning
confidence: 56%
“…We previously showed that CS administered as an intravenous infusion blocked the pulmonary vascular response to hypoxia in lambs, noting a 3% decrease in pulmonary vascular resistance during hypoxia compared to a 57% increase with placebo (12). The animals in our previous study received an intravenous loading dose of 24 mg/kg of CS before the onset of hypoxia followed by an additional 45 mg/kg during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation